Effect of amino acid balance on energy and nitrogen metabolism in growing broiler chickens - Kim, Ji-Hyuk (The University of Edinburgh, 2004)
Three experiments were performed to test the assumption that imbalanced dietary amino acid mixtures must lead to increased heat production (HP). The first experiment was based on diets formulated to have a wide range of crude protein (CP) concentrations but a fixed concentration of lysine, formulated to be the first-limiting amino acid. In the second (converse) experiment, lysine concentration was varied over a wide range while CP content was kept constant. To prevent the masking of dietary effects by thermoregulatory demands, the third experiment was performed at 30 °C with the diets similar to the diets used in the second experiment. The detailed relationships among amino acid balance, nitrogen (N) metabolism and energy (E) metabolism were investigated in a computer-controlled chamber calorimetry system. The results of experiments were compared with the predictions of a computerised simulation model of E metabolism.

In experiment 1, with constant lysine and varying CP, there was a 75% increase in N intake as CP concentration increased. This led to a 150% increase in N excretion, with no significant change in HP. Simulated HP agreed with the empirically determined results in not showing a trend with dietary CP. In experiment 2, with varying lysine but constant CP, there was a 3-fold difference in daily weight gain between the lowest and highest lysine diets. HP per bird increased significantly with dietary lysine concentration. There was still an effect when HP was adjusted for body weight differences, but it failed to maintain statistical significance. Simulated HP results agreed in showing little effect of varying lysine concentration and growth rate on HP. Based on the results of these two experiments, the third experiment was designed to test the response of birds to dietary lysine in high ambient temperature. In experiment 3 which performed at high ambient temperature (30 °C), HP per bird increased significantly with dietary lysine content, whether or not adjusted for body- weight. The trend was greater than in the previous experiment (20 °C).

To investigate the effect of amino acid balance and protein quality on growth rate and carcass characteristics, growth trial experiment was performed on a larger scale. Four diets varying CP contents were used. The results showed that there was no significant effect of high protein diet on growth rate and carcass characteristics.

A free-choice feeding experiment was also performed to investigate the sensitivity of the bird to its diet on the basis of amino acid balance, especially related to lysine concentration. Over the whole period of the experiment, birds consumed some of each diet offered, but preference was shown for the moderate or high lysine diet over the low lysine diet. Growth rate reflected total lysine intake. The birds offered the choice between Ideal Protein diet and High Protein diet consumed about 2.5 times as much of the Ideal protein diet as of the imbalanced diet.